2022
DOI: 10.1039/d2fo00243d
|View full text |Cite
|
Sign up to set email alerts
|

Digestion characteristics of quinoa, barley and mungbean proteins and the effects of their simulated gastrointestinal digests on CCK secretion in enteroendocrine STC-1 cells

Abstract: The demand for plant-based proteins has been rapidly increasing due to sustainability, ethical and health reasons. The present study aimed to investigate the digestion characteristics of three plant proteins (quinoa,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
(70 reference statements)
1
16
0
Order By: Relevance
“…Geraedts and co‐workers found that egg protein and casein hydrolysates had a significantly different ability to stimulate CCK secretion 30 . Our previous study also found that barley protein digest exhibited a potent CCK secretagogue activity, but the digests from quinoa and mungbean proteins had only a very weak effect on CCK secretion 7 . These studies suggested that different dietary proteins and degree of hydrolysis significantly affect the CCK secretagogue activity of protein hydrolysates or peptides.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Geraedts and co‐workers found that egg protein and casein hydrolysates had a significantly different ability to stimulate CCK secretion 30 . Our previous study also found that barley protein digest exhibited a potent CCK secretagogue activity, but the digests from quinoa and mungbean proteins had only a very weak effect on CCK secretion 7 . These studies suggested that different dietary proteins and degree of hydrolysis significantly affect the CCK secretagogue activity of protein hydrolysates or peptides.…”
Section: Discussionsupporting
confidence: 51%
“…reported that soybean protein hydrolysate stimulated CCK secretion and inhibited feed intake through CaSR 6 . Our previous study also found that CaSR was involved in barley protein digest‐induced CCK secretion 7 . However, it remains unclear whether CaSR is involved in wheat protein digest (WPD)‐mediated CCK secretion.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Traditionally, proteins are considered the most satiating macronutrient compared with an isoenergetic intake of carbo-hydrates and fat, 5 suggesting that dietary proteins are potential potent stimulants of CCK secretion. Several protein hydrolysates or digests from soybean, 6 milk whey, 7 barley, 8 and egg white 9 have been demonstrated to stimulate CCK secretion. However, the knowledge about CCK secretagogue activity induced by other protein hydrolysates or digests is limited.…”
Section: Introductionmentioning
confidence: 99%